KEDUDUKAN QAUL SAHABAT DALAM ISTINBAT HUKUM ISLAM Analisis Komparatif Pemikiran Ibnu Hazm dan Wahbah az-Zuhailī (THE POSITION OF QAUL SAHABAT IN ISTINBAT OF ISLAMIC LAW The Comparative Analysis of Ibnu Hazm and Wahbah az-Zuhaili’s Thought) - Muhammad Alim Khoiri (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
Qaul sahabat is one of the debatable sources of Islamic law which left pro and contra regarding its validity of hujjah. This source of law is an interesting and important topic to be discussed. Theory of qaul sahabat includes friends of the Prophet Muhammad, the selected persons and the first generation after Muhammad. This research employs a documentary study by researching data related with books written by Ibnu Hazm and Wahbah az-Zuhaili, entitled “Al-Ihkam fi Usul al-Ahkam”and “Usul al-Fiqh al-Islami”. In additions, other books are used as source of data in this paper. This study applies a comparative analyzes to examine the collected data by comparing the thought of those two figures in order to find the similarities and differences. This article concludes that both Ibnu Hazm and Wahbah az-Zuhaili deny qaul sahabat as hujjah syar’i, however both of them have different reasons on it.